A sala de aula como espaço de ressignificação da ludicidade e da amorosidade na formação docente - Carvalho, Elvio de (2014)
This research was developed in the Post-graduate Program in Education, in the Master‟s degree level and in the Formation, Knowledge and Professional development Line (LP1). It had the guidance of Professor Valdo Barcelos. The theme of this investigation is centered in the redefinition of the teacher formation and has as its focus the playfulness and the lovingness. Having as its investigative space the context of two classrooms in a public municipal school of Santa Maria, RS. We evidenced that the teacher formation doesn‟t restrict itself only to the academic context, but also to the school environment and the classroom, main place of acting and professional redefinition. In that sense, the pedagogical practice in a playful and loving perspective must a part not only of the formative perspective of the teacher, but also of his practice in the context of Basic Education. The methodology is from a qualitative nature. The project is based on three chapters: I We approach aspects of the initial formation of the teacher, having as a perspective the lovingness and playfulness as possibilities of redefinition of the instructor profession. II We develop significant aspects of the pedagogical practice in the context of the classroom as a possibility in the emancipatory formation of the child. III We verify the possibilities that the playfulness and the lovingness have to redefine the teacher practice and the child formation. Therefore, more than searching for answers, we long to consider probable information that are established as possible theoretical and epistemological contributions to mediate and construct the practices of the teacher formation. Our main goal was to contribute with the enlargement of the knowledge repertory considered necessary to the teacher practice.